2016
DOI: 10.1016/j.drudis.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors, pathogenesis and therapeutic intervention of Kawasaki disease

Abstract: Kawasaki disease (KD) is an acute febrile childhood inflammatory disease, associated with coronary artery abnormalities. The disease is believed to result from an aberrant inflammatory response to an infectious trigger in a genetically predisposed individual. KD is associated with an endothelial cell injury as a consequence of T cell activation and cytotoxic effects of various proinflammatory cytokines. Intravenous immunoglobulin (IVIG) infusion and aspirin are the standard treatment of acute KD. However, 10-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 101 publications
2
38
1
3
Order By: Relevance
“…Traditional viewpoints propose that the immune system is abnormally activated in the acute stage of KD. Blood vessels are damaged by a large number of cytokines and anti-endothelial cytotoxic antibodies (Andreozzi et al, 2017;Galeotti et al, 2016), and the level of immune globulin generally increases (Menikou, Langford & Levin, 2019). However, in this study, IgA and IgG in the peripheral blood of the KD group decreased, which may be related to the following factors.…”
Section: Discussioncontrasting
confidence: 56%
“…Traditional viewpoints propose that the immune system is abnormally activated in the acute stage of KD. Blood vessels are damaged by a large number of cytokines and anti-endothelial cytotoxic antibodies (Andreozzi et al, 2017;Galeotti et al, 2016), and the level of immune globulin generally increases (Menikou, Langford & Levin, 2019). However, in this study, IgA and IgG in the peripheral blood of the KD group decreased, which may be related to the following factors.…”
Section: Discussioncontrasting
confidence: 56%
“…KD is an acute vasculitis that predominantly targets the medium-sized arteries, particularly the coronary artery, and which leads to the development of coronary artery aneurysm if untreated with IVIG. Although IVIG therapy significantly reduces the occurrence of coronary aneurysm and the morbidity and mortality associated with KD, some patients are resistant to this therapy; thus, additional therapies are still needed 2 , 15 . In the present study, we demonstrated that IL-10 supplementation by AAV gene delivery almost completely prevented inflammatory responses, such as inflammatory cell infiltration and the expression of cytokines, and the subsequent development of cardiac fibrosis and dysfunction in CAWS-induced vasculitis, a murine model of KD.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental studies implicated a number of inflammatory cytokines are implicated in the pathogenesis of KD 2 , 15 . Among these, TNF-α is one of the most important cytokines in the development of KD.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment has been administered in IVIG-resistant patients with success regarding fever and inflammatory parameters, however, with no differences regarding cardiac disease (Burns et al, 2005, 2008; Son et al, 2011). Other immunosuppressive agents have occasionally been used such as: cyclosporine, cyclophosphamide, methotrexate, and plasma exchange in resistant KD patients to IVIG, steroids, and anti-TNFα (Galeotti et al, 2016). …”
Section: Kawasaki Diseasementioning
confidence: 99%